La microparcela de campo como un método biológico rápido para evaluar la fertilidad del suelo - Martini, J. A. (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2025)
Holme and Hardy proposed in 1944 and 1966 respectively, a field cor micro plot technique to be used as a biological method for soil analysis to protect nutrient requirements on their field conditions this technique consisted of factorial without replications and plus 64 60 centimeters with the reprints purple distributed in three rows Due to criticisms of the lack of replications, the plots being too small and the excess of treatments, a new field the microplot technique is here proposed. The new design consists of an N, P, K factorial, 23 with 3 replications and plots 100 x 100 cm with 50 plants per plot distributed in 5 rows. The plant dry weight obtained after 30 days of growth is also used instead of the green weight. It is the author´s contention that since the vegetative growth of corn at one month of age does not always correlate significantly to grain yield, the field microplots have a limited use and they should not be utilized to solve intricate problems but rather for preliminary or complementary evaluation of the nutritional status of soils. With this in mind it is felt that the factorial, 2, fully satisfies the needs. The results of field microplots, greenhouse pot experiments and conventional field plots, carried out with corn on the same soils were compared and found to correlate significantly.